Booster immunization of children with an acellular pertussis vaccine enhances Th2 cytokine production and serum IgE against pertussis toxin but not against common allergens - MILLS, KINGSTON (British Society for Immunology, 2000)
Acellular pertussis vaccines (Pa) protect against severe pertussis in children. However, serum antibody responses decline quickly after immunization. Studies in animal models suggest that cell-mediated immunity also contributes to protection against Bordetella pertussis, and it has already been demonstrated that Pa induce T cells that secrete type-1 and type-2 cytokines in children. In this study we examined the persistence of the T cell response and the effect of booster immunization in 4?6-year-old children. Cell-mediated immunity to B. pertussis antigens was detected in a high proportion of children more than 42 months after their last immunization. Peripheral blood mononuclear cells (PBMC) from the majority of children secreted interferon-gamma (IFN-?) and a smaller proportion IL-5, in response to specific antigen stimulation in vitro. However, following booster immunization, significantly higher concentrations of IL-5, but not IFN-?, were produced by PBMC in response to B. pertussis antigens. Furthermore, plasma IL-4 and IL-5 concentrations were increased, whereas IFN-? concentrations were reduced following booster immunization. It has been suggested that childhood immunization with Th2-inducing vaccines may predispose some children to atopic disease. Although we found that pertussis toxin (PT)-specific IgE was significantly increased after booster immunization in both atopic and non-atopic children, the levels of IgE to common allergens and the prevalence of positive skin prick test were unaffected by the booster vaccination. Thus, despite the enhancement of type-2 responses to B. pertussis antigens, booster vaccination with Pa does not appear to be a risk factor for allergy.
PUBLISHED
Keywords: pertussis vaccine, Th1/Th2 cell, IgE, allergens, pertussis toxin